Gustav Mahler - Richard Strauss: Correspondence 1888-1911 - Blaukopf, Herta 1924-2005; Jephcott, Edmund (London Faber and Faber, 1984)
Gustav Mahler and Richard Strauss came to know one another as young conductors in Leipzig in 1887. From then until Mahler's death in 1911 - the year of the first performance of "Der Rosenkavalier" - they kept in touch. Mahler himself described their relationship as that of two miners tunnelling from opposite directions with the hope of eventually meeting. This first publication of their correspondence, which includes 25 previously unknown Strauss letters, offers a portrait of two men who were as antithecial in their musical means and goals as in their temperaments and personalities, but who exercised a strong fascination for one another. These 63 letters show both composers advancing in their careers as they battled against adverse conditions in the musical world at the turn of the century. They present Mahler's energetic support of Strauss's "Symphonia Domestica", which Mahler conducted in 1904 and, in turn, Strauss's championing of Mahler's music, especially the Second and Third Symphonies. The correspondence is fully annotated and is supplemented with an essay by Herta Blaukopf.
Keywords: Mahler, Gustav -- 1860-1911; Strauss, Richard -- 1864-1949; 19th Century (1801-1900); 20th Century (1901-2000); Correspondence; Music history